Peranan Mebel Ariska Dalam Mengatasi Pengangguran Masyarakat Kelurahan Foabata Kecamatan Ngada Bawa Kabupaten Ngada - Yosef Moan Banda (Program Studi Pendidikan Ekonomi, Universitas Flores, 2018)
The purpose of this study was to determine the role of Ariska Furniture in overcoming the unemployment of the community in Foabata Subdistrict, Ngada Bawah District, Ngada Regency. The focus of this research is the role of Ariska Furniture the number of unemployment absorbed by Ariska’s Furniture as labor and the level of labor productivity in Ariska Furniture. The type of research used is a mixture of qualitative and quantitative methods. A qualitative approach is used to describe the role of Ariska Furniture in overcoming unemployment. While the quantitative approach is used to analyzed the certainty of the high and low of Ariska Furniture. The instrument used are observation, interviews based on the guidelines prepared and questionnaires. The calculations results, r=0,425 which is consulted with the table r product moment value for subject (N) 20 people, in a significance level of 5% = 0,514 and a significance of 1% = 0,641, it turns out the calculation results r=0,425 is smaller than the r table product value moment, both for the significance level of 5% and 1%. The results of data processing dan analysis, prove that the role of Ariska Furniture in overcoming unemployment for the people of Foabata Village, Ngada Bawah subdistrict, Ngada District is low.